2018
DOI: 10.5194/angeo-36-705-2018
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gravity wave parameters in the airglow combining photometer and imager data

Abstract: Abstract. Mesospheric airglow measurements of two or three layers were used to characterize both vertical and horizontal parameters of gravity waves. The data set was acquired coincidentally from a multi-channel filter (Multi-3) photometer and an all-sky imager located at São João do Cariri (7.4 • S, 36.5 • W) in the equatorial region from 2001 to 2007. Using a least-square fitting and wavelet analysis technique, the phase and amplitude of each observed wave were determined, as well as the amplitude growth. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In summary, we demonstrated that our analysis is capable of determining the full set of GW parameters covering a wide range of values that are known to be typical for gravity waves. Typical values for λ h in airglow data are in the range of 10 -200 km (Nakamura et al, 2003;Diettrich et al, 2005;Matsuda et al, 2014;Lu et al, 2015;Nyassor et al, 2018). By 5 analysing keograms, Fritts et al (2014) retrieve even larger λ h with values reaching 4000 km.…”
Section: Long-period Gravity Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we demonstrated that our analysis is capable of determining the full set of GW parameters covering a wide range of values that are known to be typical for gravity waves. Typical values for λ h in airglow data are in the range of 10 -200 km (Nakamura et al, 2003;Diettrich et al, 2005;Matsuda et al, 2014;Lu et al, 2015;Nyassor et al, 2018). By 5 analysing keograms, Fritts et al (2014) retrieve even larger λ h with values reaching 4000 km.…”
Section: Long-period Gravity Wavesmentioning
confidence: 99%
“…To obtain intrinsic periods, OH imaging data is often combined with meteor radar observations of the ambient wind (e.g. Nyassor et al, 2018). Mangognia et al (2016) proposed a multi-channel instrument to deduce vertical wavelengths which must otherwise be determined from the dispersion relation or in combination with other observation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The mean altitude is about 87 km and the layer has a full width at half maximum (FWHM) of about 9 km (e.g. Baker and Stair Jr., 1998;Oberheide et al, 2006). Measurements are carried out every night, except for nights with bad weather conditions.…”
Section: Measurement Datamentioning
confidence: 99%
“…Since the 1960s, MSTIDs have been widely investigated with various ground‐based techniques like ionosondes (Reinisch et al, ), radars (Fukao et al, ; Kelley & Fukao, ), using total electron content (TEC) derived from Global Navigation Satellite Systems (GNSS) measurements (Figueiredo et al, ; Hernández‐Pajares et al, ) or with all‐sky airglow imagers (Martinis et al, ; Nyassor et al, ; Otsuka et al, , ). If in situ observation of MSTIDs are widely reported, for instance, with plasma probes onboard C/NOFS (Burke et al, ) or CHAMP and DMSP‐F15 spacecrafts (Nishioka et al, ), remote sensing of MSTIDs based on airglow observations from space are, however, much less numerous.…”
Section: Introductionmentioning
confidence: 99%
“…Periodicity of such waves ranges between several hours for the main tides up to about 30 days for planetary waves. To these recurrent patterns are superimposed numerous types of disturbances which constitute the short-term Since the 1960s, MSTIDs have been widely investigated with various ground-based techniques like ionosondes (Reinisch et al, 2018), radars , using total electron content (TEC) derived from Global Navigation Satellite Systems (GNSS) measurements (Figueiredo et al, 2018;Hernández-Pajares et al, 2012) or with all-sky airglow imagers (Martinis et al, 2018;Nyassor et al, 2018;Otsuka et al, 2004Otsuka et al, , 2013. If in situ observation of MSTIDs are widely reported, for instance, with plasma probes onboard C/NOFS (Burke et al, 2016) or CHAMP and DMSP-F15 spacecrafts (Nishioka et al, 2009), remote sensing of MSTIDs based on airglow observations from space are, however, much less numerous.…”
Section: Introductionmentioning
confidence: 99%